Late‐onset presentation and phenotypic heterogeneity of the rare R377W PSEN1 mutation. (12th October 2020) - Scarioni, M.; Arighi, A.; Fenoglio, C.; Sorrentino, F.; Serpente, M.; Rotondo, E.; Mercurio, M.; Marotta, G.; Dijkstra, A. A.; Pijnenburg, Y. A. L.; Scarpini, E.; Galimberti, D.
Abstract : Background and purpose: Mutations in the PSEN1 gene are the most common cause of autosomal‐dominant Alzheimer's disease and have been associated with the earliest disease onset. We describe an unusual presentation of the rare R377W PSEN1 mutation with a late age of onset, and we provide for the first time in vivo pathological evidence for this mutation. Methods: A 71‐year‐old female patient with progressive cognitive decline in the past 3 years and positive family history for dementia underwent neurological evaluation, neuropsychological testing, lumbar puncture, conventional brain imaging, amyloid‐positron emission tomography (PET) and extensive genetic screening with a next‐generation sequencing technique. Results: The diagnostic workup revealed mixed behavioural and amnestic disease features on neuropsychological tests, magnetic resonance imaging, and 18‐fluorodeoxyglucose (FDG)‐PET. Amyloid‐PET detected amyloid deposition in the frontal areas, in the parietal lobes and the precunei. The genetic screening revealed the presence of the rare R377W mutation in the PSEN1 gene. Conclusions: Extensive genetic screening is also advisable for late‐onset presentations of Alzheimer's disease, especially in the presence of a positive family history or atypical clinical features. Abstract : Here, we describe an atypical presentation of the rare R377W PSEN1 mutation, emphasizing the unusual late age of onset and the mixed frontotemporal and parieto‐hippocampal dysfunction. In order to do so, beside a detailed clinical characterization, we provide a description of the family tree, conventional imaging findings and, for the first time, amyloid‐PET. Extensive genetic screening is advisable also for late‐onset presentations of Alzheimer's disease, especially in the presence of a positive family history or atypical clinical features.